The IIUM and the renaissance of the Ummah - Zen, Ismawi (IIUM Press, 2009)
Introduction: As one passes over the bridge that crosses the Karak Highway on the new Sg. Pusu Road, one is immediately welcomed by a panoramic view of the cluster of buildings below, with distinct blue tiled roofs and sandy textured walls. It is as if one is chancing upon the lost city of Shangrila, albeit an Islamic looking one. The columns and colonnaded corridors, the towers, the arched entrances and doors, the inner courtyards, and the lush green with rivers flowing lazily along natural corridors make one recall the great Andalusian cities of Cordova and Granada. This is the campus of the International Islamic University Malaysia (IIUM).